2003
DOI: 10.1007/s00216-003-2196-3
|View full text |Cite
|
Sign up to set email alerts
|

A multi-residue method for characterization and determination of atmospheric pesticides measured at two French urban and rural sampling sites

Abstract: The extensive use of pesticides to protect agricultural crops can result in the transfer of these compounds into the atmosphere and their diffusion towards urban areas. Precise evaluation of the geographic impact of this type of pollution is important environmentally. In this paper, analytical methods for the sampling, characterization, and determination of agricultural pesticides in air were developed; the methods were then applied in the Paris and Champagne regions. Sixteen pesticides belonging to nine chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…However, Soxhlet extraction needs high volumes of solvent and is very time-consuming -around 20 h - [10,15,23]. And there are suspicions that the more aggressive conditions of the emerging microwave-assisted extraction method may deteriorate some pesticides.…”
Section: Ultrasonic-assisted Extraction Cyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Soxhlet extraction needs high volumes of solvent and is very time-consuming -around 20 h - [10,15,23]. And there are suspicions that the more aggressive conditions of the emerging microwave-assisted extraction method may deteriorate some pesticides.…”
Section: Ultrasonic-assisted Extraction Cyclesmentioning
confidence: 99%
“…Moreover, standardized analytical methods have also been established for occupational exposure monitoring, e.g., the determination of organonitrogen pesticides in air [14]. With respect to the atmosphere, several studies have reported atmospheric concentrations of pesticides after their application in open or confined areas [6,[15][16][17][18] and individual values or temporal series in different locations -agricultural, urban and rural areas - [10,[19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, since several decades it is well known that the atmosphere, natural waters and soils are polluted worldwide by a number of polycyclic aromatic hydrocarbons (PAHs), organo-chlorinated compounds, pesticides and heavy metals at trace levels [1,2]. For example, pesticide residues and other organic micropollutants have been recently found in the air and rainwater of rural as well as urban regions of developed countries [3,4], as well as in the natural waters of many rivers and lakes [5,6]. Therefore, it is very important to establish and improve sensitive and selective analytical methods and procedures for identifying, detecting and determining pollutants in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Chromatographic, multi-residues methods remain one of the preferred tools for the characterization and determination of low levels of pollutants in the environment [3,5,6]. However, luminescence spectrometry has also been proposed for the study and determination of chemical species, and several improved luminescence analytical methods and procedures have been developed in recent years [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of documentation of procedures used to prevent and/ or quantify the extent of sample contamination, 10 studies included both field and lab blanks and are considered Tier 1 (Aulagnier et al 2008;Hines et al 2001;Messing et al 2011Messing et al , 2013Morgan et al 2008;Morgan, Wilson, and Chuang 2014;Thomas et al 2010;Waite et al 2002a;Wilson, Chuang, and Lyu 2001;Wilson et al 2010). Five studies included only field blanks (Curwin et al 2005b;Whitmore et al 1994;Yao et al 2006) or lab blanks (Baraud et al 2003;Hawthorne et al 1996) and ranked as Tier 2. The remainder did not document avoidance of sample contamination and are thus Tier 3 for this quality element.…”
Section: 4-d and Airmentioning
confidence: 99%